Barriers and Opportunities for Residential Solar PV and Storage Markets - A Western Australian Case Study - Tayal, A.; Rauland, Vanessa (2016)
Residents and businesses around the world are increasingly installing solar photovoltaic (PV) panels and battery storage systems, satisfying not just their interest in clean energy, but also taking advantage of reduced technology costs and mitigating against future electricity price rises. Solar PV panels coupled with storage systems present an opportunity to move towards a resilient, affordable, flexible and secure electricity network. Western Australia provides a unique set of conditions (isolated network, high solar radiation, and rising electricity prices), which has contributed to the rapid uptake of solar PV’s in the state. Yet, a number of issues are still obstructing the transition to renewables. Using Western Australia as a case study, this paper investigates the barriers inhibiting the network transformation and explores the role that solar PV and storage can play as a disruptive threat to the incumbent, centralised service model of electricity utilities.